Pelindungan Anak di Ruang Digital pada Momentum Regulasi 2025: Kewajiban Platform dan Tanggung Jawab Negara (SETARA : Jurnal Ilmu Hukum, 2025)
This article examines the legal obligations of digital platforms in child protection after Government Regulation Number 17 of 2025. The issue is legally important because Law Number 1 of 2024 had already imposed a duty on electronic system providers to protect children, but operational standards only became more concrete after the 2025 regulation introduced risk classification, age ranges, parental consent, age verification, reporting mechanisms, and administrative sanctions. Using normative legal research with statutory and conceptual approaches, this article maps the transition from declarative obligation to operational compliance, identifies the minimum obligations that must be fulfilled by electronic system providers, and formulates a layered responsibility model involving the state, providers, and parents or guardians. The article argues that child protection in digital spaces can no longer rest on generic safety commitments, but must be measured through specific legal duties that are auditable and enforceable.
Keywords: Child Protection; Digital Platforms; Electronic System Providers; Age Verification; Digital Governance